Textualization of "say": a functional analysis of shuō-connectives in Chinese. (3rd May 2016) - Chen, Shu-Kun
Abstract : The semantic and syntactic feature of the character shuō has been one of the central issues explored by scholars who study Chinese. However, none of their studies systematically survey why and how shuō occurs in connectives. Under the theoretical framework of SFG, this paper first introduces some critical notions of semantic domain and primitive morpheme, which help to interpret why shuō is manifested in varied grammatical environments. Then a dichotomy of lexicalized and grammaticalized shuō -connectives is proposed to illustrate how shuō "moves" into conjunctive items. A close analysis of some peculiar shuō -connectives indicates that (1) shuō marks the internal process in lexicalized items; and (2) shuō may serve as internal process, impersonal projecting process and conditional binder in grammaticalized items. It is argued that the current framework of projection semantic domain should be fine-tuned so as to take the textual manifestation into account.